2005
DOI: 10.1172/jci26020
|View full text |Cite
|
Sign up to set email alerts
|

A molecular chaperone for mitochondrial complex I assembly is mutated in a progressive encephalopathy

Abstract: NADH:ubiquinone oxidoreductase (complex I) deficiency is a common cause of mitochondrial oxidative phosphorylation disease. It is associated with a wide range of clinical phenotypes in infants, including Leigh syndrome, cardiomyopathy, and encephalomyopathy. In at least half of patients, enzyme deficiency results from a failure to assemble the holoenzyme complex; however, the molecular chaperones required for assembly of the mammalian enzyme remain unknown. Using whole genome subtraction of yeasts with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
228
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(246 citation statements)
references
References 51 publications
15
228
3
Order By: Relevance
“…Complex I catalyses the first step in the mitochondrial respiratory chain, and a homozygous mutation in this gene was found in a child with severe progressive leukoencephalopathy. 55 Disruption and functional loss or a dominant interfering effect of a mutant copy of NDUFAF2 may cause neurometabolic deficiency resulting in an allelic disorder with an ADHD phenotype. Patient 51 carries a B500 kb duplication located at 11q13.4 and inherited from the affected mother.…”
Section: Discussionmentioning
confidence: 99%
“…Complex I catalyses the first step in the mitochondrial respiratory chain, and a homozygous mutation in this gene was found in a child with severe progressive leukoencephalopathy. 55 Disruption and functional loss or a dominant interfering effect of a mutant copy of NDUFAF2 may cause neurometabolic deficiency resulting in an allelic disorder with an ADHD phenotype. Patient 51 carries a B500 kb duplication located at 11q13.4 and inherited from the affected mother.…”
Section: Discussionmentioning
confidence: 99%
“…However, genes encoding accessory subunits, such as NDUFS4, NDUFS6, NDUFA1, NDUFA2, and NDUFA11, may also contain pathogenic mutations. [8][9][10]29,30 NDUFA10 also belongs to these accessory subunits.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Furthermore, mutations have been described in eight assembly factors (NDUFAF1, NDUFAF2, NDUFAF3, NDUFAF4, C8orf38, C20orf7, ACAD9, and NDUBPL) of this complex and in an uncharacterized protein (FOXRED1) causing complex I deficiency. [9][10][11][12][13][14][15][16] Although pathogenic mutations have been described in accessory subunits, the function of these subunits is not exactly known yet. It has been suggested that some are important for the biogenesis of complex I.…”
mentioning
confidence: 99%
“…This process requires additional proteins, termed 'assembly factors', which aid complex I assembly [46]. The first pathogenic human mutation in a CI assembly factor was found in NDUFAF2 [47]. Since this initial discovery, several other pathogenic mutations have been identified in CI assembly factor genes, including NDUFAF1 [48], NDUFAF3 [49], NDUFAF4 [50], NDUFAF5 [51], NDUFAF6 [52], FOXRED1 [53], ACAD9 [54] and NUBPL [53] (Table 1).…”
Section: Oxphos Complex Imentioning
confidence: 99%